MANAJEMEN KEPALA MADRASAH DALAM MENUMBUHKAN PENDIDIKAN KARAKTER RELIGIUS SISWA MASA PANDEMI COVID-19 - Putri Lubis, Salsabila; Rambe, Nurul Zanna; Siregar, Salmah; Damanik, Amanda Geopani (Yayasan Pendidikan Islam Akmalia, 2022)
This study aims to find out how the management of madrasah principals in fostering religious character education in the digital era. This study uses a qualitative method. Head of Madrasah Tsanawiyah Ali Imron in Jl. Bersama no. 19-21, Mr. Dahlia Bdr. Congratulations for being the main sample in this study, data collection techniques using interviews, observation and documentation, data analysis of research results using reduction techniques, triangulation and drawing conclusions from research data. Based on this study, it was concluded that the management of the head of state of Madrasah Tsanawiyah in fostering religious character education in the digital era by leading to the psychological side of students which has implications for behavior, character building in children is carried out to create students who have good knowledge and behavior. The character of Tsanawiyah students has values ​​that come from Pancasila, religion, culture, and the goals of national education, namely honesty, tolerance, religious, discipline, cooperation, creativity, democracy, independence, national spirit, curiosity, love for the homeland, friendship. communicative, appreciative of achievement, love of peace, care for the environment, likes to read, cares about social, and is responsible other. The results showed that the management of the head of Madrasah Tsanawiyah in fostering religious character education had gone well with very good planning, organizing, implementing and evaluating. Information technology helps facilitate all human activities, retrieval of information, convey information and literacy about adding knowledge in learning by utilizing technology, so that students can learn by utilizing learning resources to the fullest.